PENYISIPAN GAMBAR PADA FILE PDF DENGAN METODE CHINESE REMAINDER THEOREM - Apriani, Sheila; Hasibuan, Nelly Astuti; Hutagalung, Siti Nurhabibah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The insertion of images into PDF files using the Chinese Remainder Theorem (CRT) method is one of the challenges in data security and information integrity. One effective steganography method used to hide secret messages (text or images) inside other files containing text, images, or even audio, without showing noticeable or visible changes in the quality and structure of the original file. The method used in this study allows image data to be divided into smaller parts, which are then embedded into various locations within the PDF file based on modulo operations. With this method, the image can be accurately reconstructed with high precision, even if part of the data is lost or damaged. The main advantage of this method is the increased security and confidentiality of the data, as the embedding is done in a way that is not directly visible within the PDF file, and data recovery requires specific knowledge of the CRT parameters used. The results of the study show that using CRT in the process of embedding images into PDF files is highly efficient and reconstructs the image in the PDF file without altering image quality or damaging the file structure, with better security compared to conventional methods. The potential application of this method is not only limited to image embedding but can also be extended to various other types of data.